Design and evaluation of a biological vertical shaft-subsurface ditch system for alkali spot improvement - Jifang E; Shuqing Yang; Wanfeng Zhang; Xi Chen; Qiuying Gu (Agricultural Water Management)
Alkali spots significantly hinder land productivity and agricultural growth in arid soda-alkali regions with deep water tables. We evaluated a 4-year experiment in the Xiliaohe Plain using a biological vertical shaft-subsurface ditch system (B-S system) to assess its efficacy in drainage, alkalinity reduction, desalination, and maize yield enhancement. The system’s design integrates vertical bio-shafts (1.2 m depth) with subsurface ditches (30 cm width, 5 % slope), backfilled with uncrushed maize straw to enhance porosity. This configuration uniquely combines horizontal drainage and vertical infiltration, disrupting the impermeable alkali layer. An untreated alkali spot was designated as the control (CK treatment) for comparison. The results showed that with increasing years of B-S treatment, alkalinity and soil salinity in alkali spots decreased significantly. Reductions in salinity and alkalinity followed a symmetrical pattern around the subsurface ditches and shafts, weakening with distance from these features. On that basis, four dynamic soil water-salt control zones gradually formed around the alkali spots. Compared to CK treatment, the B-S treatment increased drainage speed by 1.09 times and reduced the average depth of waterlogging in alkali spots by 50 %. Meantime, the B-S treatment effectively contributed to groundwater recharge, and the average increase of groundwater level was 0.09 m in the three consecutive years of monitoring. Soil improvement results indicated a 59.9 % reduction in soil salinity and a 78.8 % decrease in alkalinity within the 0–30 cm cultivation layer. The B-S system improved soil physicochemical properties, fostering better maize growth conditions. As a result, maize seedling emergence increased by 19.9 %, seedling retention rate by 84.5 %, and yield by 78.1 %. The B-S system’s radial layout and straw-mediated permeability offer a sustainable alternative to conventional drainage in arid regions. It provided theoretical and scientific support for alkali spot management and the sustainable use of soil and water resources, offering new strategies for promoting regional agricultural sustainability.